Polymerized stimuli-responsive microgel hybrids of silver nanoparticles as efficient reusable catalyst for reduction reaction - Pany, Biswajit; Majumdar, Amrito Ghosh; Bhat, Suresh; Si, Satybrata; Yamanaka, Junpei; Mohanty, Priti S. (Heliyon, 2024)
We have showcased the potential of polymerized hydrogels (PGMs) with uniform -sized stimuliresponsive microgel particles as promising alternatives to prevent aggregation in solution based nanoparticle systems. In the current work, we implemented the PGM concept by embedding anionic stimuli -responsive microgels (PNIPAM-co-AAc)-silver (Ag) hybrids within a hydrogel matrix. These PGM@AgNP hybrid materials are used as catalysts for the reduction of 4-nitrophenol (4 -NP) to 4-aminophenol (4 -AP) in the presence of sodium borohydride. UV-VIS spectroscopy is used for studying catalytic activity. In the solution based system, the complete reduction of 4NP to 4 -AP took 30 minutes with pure Ag nanoparticles, 24 minutes with PNIPAM-Ag hybrid (Neutral) microgels and 15 minutes with PNIPAM-co-AAc-Ag (Anionic) hybrid microgels. In contrast PGM containing PNIPAM-co-AAc-Ag hybrids achieved full reduction in just 15 minutes, along with a 3 -minute induction period. For pure Ag nanoparticles, the first -order rate constant is found to be 0.25 min - 1, for PNIPAM-Ag hybrid (Neutral), it is 0.21 min- 1 and for PNIPAM-coAAc-Ag (Anionic), it is 0.5 min- 1 where as for PGM containing anionic microgel hybrids it is found to be 0.8 min - 1. Furthermore, the reusability of the PGM-Ag (anionic) materials for catalytic activity remains unaltered even after several washings. In summary, our study highlights the effectiveness of PGM@AgNP materials as efficient catalysts for the reduction of 4-nitrophenol to 4-aminophenol, indicating their versatile potential in various catalytic applications.
Keywords: Light scattering; Microgel-metal hybrids; Nanomaterial catalysts; PNIPAM microgels; Polymerized hydrogel matrix(PGM; Stimuli-responsive microgels